Innovating surgical practice and policy: lessons learnt from the second Oxford Surgical Innovation Conference: Invited Editorial - Hoppe, Solveig; de Andres Crespo, Marta; Williams, Matthew; Handa, Ashok; McVeigh, James (Journal of the Nuffield Department of Surgical Sciences, 2020)
The section on changes in training from the Future in Surgery Report by the Royal College of Surgeons of England outlined key ideas for improving surgical training in the future. These ideas included the use of augmented reality, virtual reality and simulation, as well as increased support for surgeons to diverge from traditional surgical training pathways to undertake research and act as entrepreneurs. The Second Oxford Surgical Innovation Conference (OxSI) had similar aims to prepare delegates for these changes in surgery. The event took place on Friday 13th March 2020 at St Catherine's College, Oxford, and included talks and workshops from world-renowned surgeons, which covered a vast range of topics but ultimately all gave a fascinating insight into what is needed to improve surgical practice and policy.